Optimizing Classroom Engagement: Improving Student Focus and Participation Using the Talking Stick Learning Model - Ayu Irani Oktavianti Seofeto; Seruni Cerah Zebua; Friska Sotania Bate’e; Arozatulo Bawamenewi; Imansudi Zega (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research aims to investigate methods to enhance student engagement and attentiveness during classroom instruction. Specifically, it explores the effectiveness of the talking stick learning model in fostering active listening among students. Adopting a qualitative approach with a phenomenological lens, this study examines the experiences of a group of students in utilizing talking sticks during classroom interactions. Through direct observation and interviews, data were collected to assess students' level of involvement, focus, and participation following the implementation of the talking stick model. The findings reveal that the majority of students (29 out of 32) demonstrated improved listening skills with the implementation of the talking stick method, indicating its potential efficacy in enhancing classroom dynamics. This study sheds light on innovative strategies to promote student engagement and active learning.